Learn iTunes Mac video training - Garay, Paul.; Kaye, Michael; Safari eBooks ([S.l.] : Peachpit Press, 2010)
"Anyone who owns an iPod, iPhone, or Apple TV uses iTunes. Not only is iTunes 8 a fantastic media player on your Mac or PC, but it is also the essential link to transferring music & videos from your computer to your digital devices. Learn how to organize your stuff by creating smart playlists, finding podcasts, syncing your calendars and contacts (even from your PC) to your iPod/iPhone, or even rent a show to watch on your Apple TV. Let us teach you all that iTunes can do from A through Z."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Dec. 8, 2010).
Keywords: Mac OS; Macintosh (Computer); iTunes; Electronic books